Postmortem diagnosis of sepsis: A preliminary immunohistochemical study with an anti-procalcitonin antibody. (September 2017) - Maiese, Aniello; Del Nonno, Franca; Dell'Aquila, Marco; Moauro, Mario; Baiocchini, Andrea; Mastracchio, Antonio; Bolino, Giorgio
Highlights: An anti-procalcitonin antibody for immunohistochemistry study. Novel strategy for postmortem diagnosis of sepsis. Procalcitonin immunohistochemical marker for postmortem diagnosis of sepsis.